Analisis Minat Siswa dan Faktor-Faktor yang Mempengaruhinya dalam Mengikuti Program Asrama Tahfidz Al-Kautsar di Madrasah Aliyah Negeri 1 Baubau - L.M. Ferdiansyah Rahmad; Maudin Maudin; Rusli Rusli (CV. ALIM'SPUBLISHING, 2026)
This study examines students’ interest in participating in the Al-Kautsar Tahfidz Dormitory Program at MAN 1 Baubau and identifies the factors influencing their participation. The study also seeks to provide a deeper understanding of how both internal and external conditions shape students’ willingness to engage in the program. Using a qualitative descriptive approach, data were collected through semi-structured interviews with dormitory supervisors, participating students, and non-participating students. Additional supporting information was also gathered through informal discussions and observation in the dormitory environment to strengthen the data validity. Data were analyzed through data reduction, data presentation, and conclusion drawing in an iterative process to ensure accurate interpretation. The findings indicate that students’ interest is shaped by internal factors, such as religious motivation, the desire to memorize the Qur’an, and self-improvement, as well as external factors, including parental support, peer influence, program socialization, and the religious dormitory environment. Conversely, low interest is associated with limited family support, low self-confidence in Qur’anic literacy, competing activities outside school, and perceptions of a demanding dormitory schedule. Overall, the program contributes positively to students’ religious character, discipline, and Qur’anic memorization skills, although variations in student interest remain evident depending on their personal and environmental conditions.